1976
DOI: 10.1007/bf00222158
|View full text |Cite
|
Sign up to set email alerts
|

The relation between cell proliferation, differentiation and ultrastructural development in rat intestinal epithelium

Abstract: The ultrastructural development of the principal cells in rat small intestine was studied by morphometric analyses in relation to the exact cell position along crypt and villus. From the bottom to the tip of the crypt, a gradual increase occurred in absolute size of the total cell, the cytoplasm, the terminal web and of nearly all cell organelles. Also, the relative size of the cytoplasm, mitochondria, microvilli and endoplasmic reticulum increased during crypt cell differentiation. No sudden changes in ultras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0
1

Year Published

1981
1981
1996
1996

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 31 publications
4
38
0
1
Order By: Relevance
“…This hypothesis proposed that the cells emerging from the crypt mouths were already deficient in enzyme machinery. The rationale for the idea was that, whereas in normal intestine, cellular proliferation takes place in the lower two thirds of the crypts and maturation starts in the upper third of this structure [23], the proliferative compartment in a hyperplastic mucosa is extended to the whole crypt region [22], with the result that part of the maturation process is suppressed. In the present case, however, this situation does not appear to arise: Recent quantitative histochemical data [7] have suggested that the operational kinetic parameters governing two disaccharidases at the base of the villi do not differ greatly between controls and ileal remnants, whereas the development of the enzymes during migration along the villi is defective in ileal remnants, at least in the case of c~-glucosidase.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis proposed that the cells emerging from the crypt mouths were already deficient in enzyme machinery. The rationale for the idea was that, whereas in normal intestine, cellular proliferation takes place in the lower two thirds of the crypts and maturation starts in the upper third of this structure [23], the proliferative compartment in a hyperplastic mucosa is extended to the whole crypt region [22], with the result that part of the maturation process is suppressed. In the present case, however, this situation does not appear to arise: Recent quantitative histochemical data [7] have suggested that the operational kinetic parameters governing two disaccharidases at the base of the villi do not differ greatly between controls and ileal remnants, whereas the development of the enzymes during migration along the villi is defective in ileal remnants, at least in the case of c~-glucosidase.…”
Section: Discussionmentioning
confidence: 99%
“…In the functional zone of crypts, and on villi, cells show changes in nuclear size, cell size, organelle content and brush border enzyme activity [1,3,7,8,12,15,28,39,44,[48][49][50].…”
Section: Vertical Differencesmentioning
confidence: 99%
“…This region also contains the characteristic differentiated Paneth cells (PC), and between the Paneth cells there are flattened, undifferentiated crypt base columnar cells (BCC), sometimes called intercalated cells, an unknown fraction of which may act as stem cells (Cheng et al, 1969;Van Dongen et al, 1976;Bjerknes and Cheng, 1981a-e).…”
Section: Introductionmentioning
confidence: 97%